POETIC TEXT AS COMMUNICATIVE-AESTHETIC CATEGORY - S. N. Bredikhin; L. P. Davydova (Гуманитарные и юридические исследования)
The article studies peculiar features of aesthetic-communicative senses in poetic texts. The key factors of realizing the deep aesthetic sense at the stage of text formation are the language norm, functional stylistic and genre features, situational character of text formation, idea and aesthetic intention, individual author's cognitive evaluative system; at the stage of perception these are temporal framework of text formation and perception, recipient's intentions, idea and aesthetic images and their resonance, or the lack of the latter as regards the idea and aesthetic purpose of the text.